2007
DOI: 10.1021/jf071131n
|View full text |Cite
|
Sign up to set email alerts
|

Yucca gloriosa:  A Source of Phenolic Derivatives with Strong Antioxidant Activity

Abstract: On the basis of the biological activities exhibited by the phenolic constituents of Yucca schidigera, the antioxidant activity of the methanol extract of Yucca gloriosa roots was evaluated in the TEAC assay. The strong activity exerted by this extract prompted investigation of its phenolic constituents, yielding three new phenolic derivatives, gloriosaols C, D, and E, along with gloriosaols A and B previously isolated from Y. gloriosa roots and yuccaols C-E isolated from Y. schidigera. ESIMS and NMR data of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 17 publications
2
31
0
Order By: Relevance
“…It is noteworthy that a high accuracy in reproducing the experimental chemical shifts is provided by this level of theory, which has proved successful in the configurational analysis of several natural compounds. [27,28,29,30] Because such accuracy is seldom observed on sp 2 carbon atoms, they have not been reported and considered in the configurational assignment in the present paper and in our preceding contributions reported in the literature. [29] In particular, for what concerns 13 C calculated results, we have considered the δ parameter (differences in experimental vs calculated 13 C NMR chemical shifts) and the MAE parameter (MAE = [|δ exp − δ calc |]/n, summation through n of the absolute values of the differences in the corresponding experimental and calculated 13 C chemical shifts); such parameters have been successfully used in the characterization of unknown stereostructures by us and by other research groups.…”
Section: Resultsmentioning
confidence: 88%
“…It is noteworthy that a high accuracy in reproducing the experimental chemical shifts is provided by this level of theory, which has proved successful in the configurational analysis of several natural compounds. [27,28,29,30] Because such accuracy is seldom observed on sp 2 carbon atoms, they have not been reported and considered in the configurational assignment in the present paper and in our preceding contributions reported in the literature. [29] In particular, for what concerns 13 C calculated results, we have considered the δ parameter (differences in experimental vs calculated 13 C NMR chemical shifts) and the MAE parameter (MAE = [|δ exp − δ calc |]/n, summation through n of the absolute values of the differences in the corresponding experimental and calculated 13 C chemical shifts); such parameters have been successfully used in the characterization of unknown stereostructures by us and by other research groups.…”
Section: Resultsmentioning
confidence: 88%
“…This confirms that radical formation and removal are in dynamic equilibrium. Methanol extract of Yucca gloriosa roots or Yucca aloifolia leaves exhibited strong radical scavenging activity (Bassarello et al 2007;Sobia et al 2013). Kucukkurt et al (2008) reported MDA levels in blood of the rats significantly decreased in groups fed diet added 100 or 200 ppm yucca powder compared to control.…”
Section: Discussionmentioning
confidence: 99%
“…TEAC assay and ESIMS, NMR data confirmed that gloriosaols A-E extracted from Y. gloriosa has antioxidant activity. 11,12 Y. schidigera and Y. gloriosa roots and barks contained these bioactive phenolics. 13 The protective effects of Y. schidigera was assessed against oxidative damage induced by acute nitrite intoxication in murine models.…”
Section: Antioxidantmentioning
confidence: 94%